Chemotherapy after immune checkpoint inhibitor failure in metastatic melanoma: a retrospective multicentre analysis - Goldinger, Simone M.; Buder-Bakhaya, Kristina; Lo, Serigne N.; Forschner, Andrea; McKean, Meredith; Zimmer, Lisa; Khoo, Chloe; Dummer, Reinhard; Eroglu, Zeynep; Buchbinder, Elizabeth I.; Ascierto, Paolo A.; Gutzmer, Ralf; et al. (European journal of cancer, 2022)
Introduction - Despite remarkably improved outcomes with immune checkpoint inhibition, many patients with metastatic melanoma will eventually require further therapy. Chemotherapy has limited activity when used first-line but can alter the tumour microenvironment and does improve efficacy when used in combination with immunotherapy in lung cancer. Whether chemotherapy after checkpoint inhibitor failure has relevant activity in patients with metastatic melanoma is unknown. - Methods - Patients with metastatic melanoma treated with chemotherapy after progression on immunotherapy with checkpoint inhibitors were identified retrospectively from 24 melanoma centres. Objective response rate (ORR), progression-free survival (PFS), overall survival (OS) and safety were examined. - Results - In total, 463 patients were treated between 2007 and 2017. Fifty-six per cent had received PD-1-based therapy before chemotherapy. Chemotherapy regimens included carboplatin + paclitaxel (32%), dacarbazine (25%), temozolomide (15%), taxanes (9%, nab-paclitaxel 4%), fotemustine (6%) and others (13%). Median duration of therapy was 7.9 weeks (0-108). Responses included 0.4% complete response (CR), 12% partial response (PR), 21% stable disease (SD) and 67% progressive disease (PD). Median PFS was 2.6 months (2.2, 3.0), and median PFS in responders was 8.7 months (6.3, 16.3), respectively. Twelve-month PFS was 12% (95% CI 2-15%). In patients who had received anti-PD-1 before chemotherapy, the ORR was 11%, and median PFS was 2.5 months (2.1, 2.8). The highest activity was achieved with single-agent taxanes (N = 40), with ORR 25% and median PFS 3.9 months (2.1, 6.2). Median OS from chemotherapy start was 7.1 months (6.5, 8.0). Subsequent treatment with checkpoint inhibitors achieved a response rate of 16% with a median PFS of 19.1 months (2.0-43.1 months). No unexpected toxicities were observed. - Conclusion - Chemotherapy has a low response rate and short PFS in patients with metastatic melanoma who have failed checkpoint inhibitor therapy, although activity varied between regimens. Chemotherapy has a limited role in the management of metastatic melanoma.